Generation of isolated attosecond pulses in the far field by spatial filtering with an intense few-cycle mid-infrared laser - Jin, Cheng; Le, Anh-Thu; Trallero-Herrero, Carlos A.; Lin, C. D. (My University, 2011)
We report theoretical calculations of high-order harmonic generation (HHG) of Xe with the inclusion of multielectron effects and macroscopic propagation of the fundamental and harmonic fields in an ionizing medium. By using the time-frequency analysis we show that the reshaping of the fundamental laser field is responsible for the continuum structure in the HHG spectra. We further suggest a method for obtaining an isolated attosecond pulse (IAP) by using a filter centered on axis to select the harmonics in the far field with different divergence. We also discuss the carrier-envelope-phase dependence of an IAP and the possibility to optimize the yield of the IAP. With intense few-cycle mid-infrared lasers, this offers a possible method for generating isolated attosecond pulses.